ANALISIS HASIL BELAJAR MATA PELAJARAN DESAIN BUSANA DAN FAKTOR- FAKTOR YANG BERPENGARUH PADA SISWA SMK NEGERI 2 GOWA - Nur Widya Anriyana; Muhammad Ardi; Hamidah Suryani (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
The purposes of the study are to discover: the learning outcomes in Fashion Design subject; the motivation, attitude, creativity, and parental support of students studying in Fashion Design; the influence of learning motivation on learning outcomes of Fashion Design; the influence of students’ attitudes on the results of Fashion Design learning; the influence of creativity on learning outcomes of Fashion Design; the influence of parental support on learning outcomes of Fashion Design; and the influence of learning motivation, attitude, creativity, and parental support collectively on learning outcomes of Fashion Design subject in SMK 2 Gowa. This type of research is a correlational quantitative research and the sampling technique used is Krejcie table based on the simple randomsampling method. Thus, the number of samples taken for this study were 56 people. Data collection techniques employed questionnaires and documentation. Data analysis used were descriptive analysis, classical assumption test, and hypothesis testing. The results of the study reveal that the learning outcomes of Fashion Design were in very high category; the learning motivation, attitude, creativity, and parental support in studying fashion design are in high category; the motivation has a significant influence on learning outcomes of Fashion Design; the attitudes have a significant influence on learning outcomes of Fashion Design; the creativity has a significant influence on learning outcomes in Fashion Design; the parental support has a significant influence on learning outcomes of Fashion Design; collectively, the motivation, attitudes, creativity, and parental support have significant influences onlearning outcomes of Fashion Design at SMK Negeri 2 Gowa.